Kontribusi Halal Value Chain dalam Pengembangan Ekonomi Syariah pada UMKM - Desy Arum Sunarta; Nurfadilah Maulana; Riski Apriliani (STAI DDI Pinrang, 2024)
The global Islamic economy industry focuses on highly consumptive and competitive sectors, such as food, lifestyle, tourism, and finance. The principle of halal serves as a universal indicator for Muslims regarding product quality and living standards. Therefore, it is crucial to start with halal raw materials and maintain integrity throughout the entire halal supply chain. The implementation of a halal value chain for all products is a form of trust for all producers. The distribution and marketing of halal food and beverage products must indicate the Shariah values and must not be mixed with non-halal products. This research aims to explore the development of the Islamic economy through the support of halal value chain implementation and to analyze data on the growth of halal certification among MSMEs in Indonesia, particularly in South Sulawesi. This study used a literature review method, gathering references relevant to the research topic. The findings indicate that the support for the halal value chain does not stop at distribution and marketing but also requires strengthening Islamic financial institutions, regulations, and research development. Aspects such as protection, impartiality, legal certainty, transparency, effectiveness, and efficiency are highly valued in ensuring the halal guarantee of a product. For Muslim consumers, halal certification is essential as it integrates religious values with consumer rights.